DACH1 Is a Cell Fate Determination Factor That Inhibits Cyclin D1 and Breast Tumor Growth - Wu, Kongming (American Society for Microbiology, 2006)
Obstacles to the expansion of cells with proliferative potential include the induction of cell death, telomere-based senescence, and the pRb and p53 tumor suppressors. Not infrequently, the molecular pathways regulating oncogenesis recapitulate aberrations of processes governing embryogenesis. The genetic network, consisting of the dachshund (dac), eyes absent (eya), eyeless, and sine oculis (so) genes, regulates cell fate determination in metazoans, with dac serving as a cointegrator through a So DNA-binding factor. Here, DACH1 inhibited oncogene-mediated breast oncogenesis, blocking breast cancer epithelial cell DNA synthesis, colony formation, growth in Matrigel, and tumor growth in mice. Genetic deletion studies demonstrated a requirement for cyclin D1 in DACH1-mediated inhibition of DNA synthesis. DACH1 repressed cyclin D1 through a novel mechanism via a c-Jun DNA-binding partner, requiring the DACH1 α-helical DS domain which recruits corepressors to the local chromatin. Analysis of over 2,000 patients demonstrated increased nuclear DACH1 expression correlated inversely with cellular mitosis and predicted improved breast cancer patient survival. The cell fate determination factor, DACH1, arrests breast tumor proliferation and growth in vivo providing a new mechanistic and potential therapeutic insight into this common disease.